NLRP6 Inflammasome Ameliorates Brain Injury after Intracerebral Hemorrhage - Wang, Peng-Fei; Li, Zhen-Guang; Zhang, Yong; Ju, Xiao-Hua; Liu, Xin-Wu; Zhou, Ai-Ming; Chen, Jing (Frontiers in Cellular Neuroscience, 2017)
NLRP6 inflammasome, one of the important intracellular innate immune sensors, has been shown to regulate immune responses. However, its roles in the intracerebral hemorrhage (ICH) are completely not clear. In the present study, we investigated the expression profile and biological roles of NLRP6 inflammasome in perihematomal brain tissues of mice subjected to ICH. In this study, we investigated the expression profile of NLRP6 inflammasome in the perihematomal brain tissues and explored the biological role of NLRP6 inflammasome upon acute brain injury in mice subjected to ICH. Increased expression of NLRP6 inflammasome was found in perihematomal brain tissues ranging from 6 h to 3 d, with a peak level at 1 d after ICH. Immunohistochemistry staining also showed that NLRP6 inflammasome was significantly increased in the perihematomal brain tissues at 1 d after ICH. Moreover, immunofluorescence staining showed that NLRP6 inflammasome was mainly colocalized in GFAP-positive astrocytes, while with little colocalized expression in NeuN-positive neurons and without expression in CD11b-positive microglia and CD31-positive endothelial cell in the perihematomal brain tissue of mice after ICH. Furthermore, NLRP6-/- ICH mice exhibited significantly higher brain water contents, proinflammatory cytokines, NF-κB activity and neurological deficit scores when compared with the wild type ICH mice. In addition, we found that TLR4-/- mice, as well as the TAK242 treated mice, had markedly lower expression of NLRP6 inflammasome expression in the perihematomal brain tissue at 1 d after ICH. Our data suggest that the upregulated NLRP6 inflammasome in perihematomal brain tissues attenuates ICH-induced brain injury.